An Autonomous Clutter Inspection Approach for Radiological Survey Using Mobile Robot - Aira N.; Salleh K.; Hamid N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Clutter (information theory); Cost effectiveness; Inspection; Mapping; Mobile robots; Radar clutter; Surveys; Clutter; Emergency response; Hotspots; Performance; Radiation intensity; Radiation mapping; Radiological emergency; Real- time; Robot kinematics; Radiation